The Legal Effectiveness of Government’s Role in Managing Parking Revenue in Batam and Its Impact on Local Government Revenue - Mahardihka, Delvin Shakira; Alhakim, Abdurrakhman; Situmeang, Ampuan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Parking is an activity regulated by the government as a source of local revenue to support infrastructure development. The management of parking revenue in Batam City refers to Law Number 28 of 2009 on Local Taxes and Levies and Local Regulation of Batam City Number 1 of 2024. The problem of this research is the effectiveness of the government's role in managing parking revenue in Batam City, especially in the aspects of facilities, community participation, and culture of legal compliance. This research aims to analyze the role of government in managing parking revenue in Batam City. The method used is empirical juridical research involving in-depth interviews with the Local Revenue Agency, Transportation Agency, as well as parking attendants in Batam City with statutory approach, conceptual approach and sociological approach. The results show that the government has a strategic role in ensuring that parking revenue is optimally distributed, both for the welfare of parking attendants and the development of city infrastructure. In addition to effective regulations, the main challenges in optimizing the parking system in Batam City lie in improving facilities, public participation, and strengthening the culture of compliance with parking regulations. Therefore, synergy between government policies, especially related to technology and public education, is needed to create a parking system that is more transparent, efficient, and contributes maximally to local revenue.